Pengembangan LKPD Berbasis Kemampuan Berpikir Kritis pada Materi Pecahan di Kelas V SDN 34 Pontianak Selatan - Deswanti, Lamberta; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda; Kresnadi, Hery; Salimi, Asmayani (AS-SABIQUN, 2023)
The study aims to produce worksheet based on students critical thinking skills on addition and subtraction of fractions whit different denominators in class V SDN 34 South Pontianak. Research and development (RnD) methods by adapting the Thiagarajan development model (define, design, development and dissemination). The data sources for this research were the results of the validation of 3 validators, the results of the practicality questionnaire, and the result of the student worksheet trials. The data collection technique for this research was a validator validation questionnaire, practicality questionnaire, and test questions for students. The result of the study show that during the process of developing LKPD based on critical thinking skills, there are four stages, namely define, design, development and dissemination. The validity of the average percentage of LKPD from the learning aspect (material) is 83% whit very valid criteria, from the appearance (design) aspect it is 74% with valid criteria, and the aspect of conformity with critical thinking skills is 90% whit very valid criteria. The practicality of using LKPD based on small-scale critical thinking skills is 3,9 in the practical category, and the practicality of using LKPD based on large scale critical thinking skills is 3,9 in the practical category. The mastery level of small scale trials obtained an average percentage of 100% completeness whit very high criteria and large-scale trials obtained an average percentage of 85,7% completeness with very high criteria.